Development of Flipbook-Assisted Practical Guide on Measurement Physics Materials to Increase Junior High School Student Learning Motivation - Dewi Masyitha; Suyanta Suyanta; Jumadi Jumadi; Shofia Maghfiroh (Jurnal Penelitian Pendidikan IPA, 2023)
Science learning is a learning process that emphasizes natural phenomena and their relationships. This development research aims to determine the feasibility of a flipbook-assisted practicum guide that has been made, and to determine students' learning motivation using flipbook media on measuring physics material which is associated with measuring ideal body weight. The instrument used was 20 students from SMP Negeri 5 Jombang Class VII F. The results obtained were validation of media experts and material experts with a summary of aspects obtained by an average of 84.25% with a very good category. For the validation of the student response questionnaire the average percentage of 89.75% in the very good category. And the results of the student learning motivation response questionnaire with 3 aspects of the assessment averaged 84.60% in the very good category, so this flipbook-based media can be used to increase the motivation of junior high school students in measuring practicum